A RETROSPECTIVE REVIEW OF THE DEVELOPMENT OF PHYSICAL TRAINING MODELS FOR THE SECURITY AND DEFENSE SECTOR SPECIALISTS - Гнидюк, О. (Київський національний університет імені Тараса Шевченка, 2021)
The article establishes that the main factor determining the emergence and justification of new models of physical training is a change in the nature and methods of combat operations. It has been established that in professional armies, as a rule, the "conditioned" model of physical training is implemented, in mixed type armies – the "sports" model, and in conscription armies the "military-applied" and "gymnastic" models are realized. At the current stage of development and functioning of the components of the security and defense sector there exist "conditional" (specially developed for professional armies) and "sports" models (for military formations and law enforcement bodies, staffed according to the principle of mixed staffing – contract servicemen and conscripts). The conditional model of physical training is a practical embodiment of the concept of "total physical readiness", developed in the United States under the influence of insights into the nature of modern warfare and the characteristics of combat operations. This concept, in various modifications, has been adopted by other NATO members. The concept was formed during the modernization of combat and physical training in connection with the transition to the professional method of manning the U.S. armed forces. This concept is based on the experience of past wars, ideas about the characteristic features of modern warfare and the consequent requirements for the physical training of troops, as well as the achievements of science and practice in the field of physical culture and sports. A close correlation between physical and mental readiness of servicemen has been established. The psychological orientation of physical training involves the development of moral and volitional qualities of military personnel in order to increase resistance to the effects of combat stress. The concept of mobilization was developed mainly for armies with a mixed method of manning. The use of a sports model of physical training provides the greatest motivation for military personnel to engage in physical exercises and achieve high results, as well as helping to level out differences between different categories of personnel.

З'ясовано, що основним чинником, який визначає появу та обґрунтування нових моделей фізичної підготовки, є зміни характеру і способів ведення бойових дій. Встановлено, що у професійних арміях реалізується "кондиційна" модель фізичної підготовки, в арміях змішаного типу – "спортивна", а в призовних арміях – "військово-прикладна" і "гімнастична" моделі. На сучасному етапі розвитку та функціонування складових сектора безпеки та оборони найбільш поширені "кондиційна" (спеціально розроблена для професійних армій) і "спортивна" (для військових формувань і правоохоронних органів, що комплектуються за принципом змішаного комплектування – контрактниками і призовниками) моделі. Кондиційна модель фізичної підготовки – практичне втілення концепції "повної фізичної готовності", розробленої у США під впливом уявлень про характер сучасної війни та особливості бойових дій. Ця концепція в різних модифікаціях була прийнята іншими членами НАТО. Вона сформувалася у процесі модернізації системи бойової та фізичної підготовки у зв'язку з переходом до професійного способу комплектування збройних сил США. В її основі лежать досвід минулих воєн і уявлення про характерні особливості сучасної війни та вимоги до фізичної підготовки військ, що випливають звідси, а також досягнення науки і практики в галузі фізичної культури і спорту. Встановлено тісний взаємозв'язок між фізичною і психічною готовністю військовослужбовців. Психологічна спрямованість фізичної підготовки передбачає виховання морально-вольових якостей військовослужбовців з метою підвищення стійкості до впливу бойового стресу. Концепцію мобілізації розроблено переважно для армій зі змішаним способом комплектування. Застосування спортивної моделі фізичної підготовки забезпечує найбільшу мотивацію військовослужбовців до занять фізичними вправами, досягнення ними високих результатів, а також сприяє нівелюванню відмінностей між різними категоріями особового складу.
РЕТРОСПЕКТИВНИЙ ОГЛЯД РОЗВИТКУ МОДЕЛЕЙ ФІЗИЧНОЇ ПІДГОТОВКИ ФАХІВЦІВ СЕКТОРА БЕЗПЕКИ ТА ОБОРОНИ
Keywords: модель фізичної підготовки; концепція фізичної підготовки; фахівці сектора безпеки та оборони; професійна підготовка; фізична підготовленість; physical training model; physical training concept; specialists in the security and defense sector; professional training; physical preparedness